2018
DOI: 10.1128/jvi.02080-17
|View full text |Cite
|
Sign up to set email alerts
|

Glycosyl-Phosphatidylinositol-Anchored Anti-HIV Env Single-Chain Variable Fragments Interfere with HIV-1 Env Processing and Viral Infectivity

Abstract: In previous studies, we demonstrated that single-chain variable fragments (scFvs) from anti-human immunodeficiency virus (HIV) Env monoclonal antibodies act as entry inhibitors when tethered to the surface of target cells by a glycosyl-phosphatidylinositol (GPI) anchor. Interestingly, even if a virus escapes inhibition at entry, its replication is ultimately controlled. We hypothesized that in addition to functioning as entry inhibitors, anti-HIV GPI-scFvs may also interact with Env in an infected cell, thereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 80 publications
(97 reference statements)
1
6
0
Order By: Relevance
“…It has been reported that processed HIV-1 gp120/gp41, but not gp160, is preferentially incorporated into virions via MA-dependent mechanisms (37, 38). Our current results are consistent with this model, showing that impaired gp160 cleavage in the absence of Vpr leads to reduced levels of gp120/gp41 and thus lower levels of gp120/gp41 in the virion (24, 3942). As we have previously reported, reduced gp120/gp41 in the virions led to reduced infectivity of virions (defined as infectious activity per virion particle) (43, 44).…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that processed HIV-1 gp120/gp41, but not gp160, is preferentially incorporated into virions via MA-dependent mechanisms (37, 38). Our current results are consistent with this model, showing that impaired gp160 cleavage in the absence of Vpr leads to reduced levels of gp120/gp41 and thus lower levels of gp120/gp41 in the virion (24, 3942). As we have previously reported, reduced gp120/gp41 in the virions led to reduced infectivity of virions (defined as infectious activity per virion particle) (43, 44).…”
Section: Discussionsupporting
confidence: 92%
“…If positive, supernatants were passed through 0.45-μm syringe filters, aliquoted, and frozen at −80°C. The infectious titers of the stocks were determined by limiting dilution infection analysis using TZM-bl reporter cells and luciferase assay as described ( Misra et al, 2018 ). Infectious virus recovered from CD4 + T cells at 196 and 200wpi was named C/196 and C/200, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies suggested that GPI-anchored anti-gp120 scFv X5 (GPI-X5) and nanobody (GPI-m36.4) can interfere with the expression and processing of viral Env glycoproteins and the infectivity of progeny HIV-1virions, underlying a multifaceted mode of antiviral action [ 26 , 36 ]. Herein, we also utilized similar experimental protocols to characterize the antiviral mechanism of GPI-10E8.…”
Section: Resultsmentioning
confidence: 99%